Sertifikasi Halal dan Implikasinya Bagi Bisnis Produk Halal di Indonesia - Warto Warto; Samsuri Samsuri (Prodi Perbankan Syariah FAI UMT, 2020)
This paper aims to determine the implications of halal certification for the halal product business in Indonesia. The issue of halal has become a global trend marked by the presence of halal certification institutions in various parts of the world. This paper uses descriptive qualitative methods through a review of relevant literature and observations of the practice of implementing halal guarantee systems in Indonesia. Data obtained through journals, books, magazines, newspapers, electronic media, such as the official website of LPPOM MUI and personal communication with competent sources. The results showed that the certification of halal products has positive implications in building a halal business climate in Indonesia. For consumers, halal certification provides protection, guarantees, product halal information and becomes an instrument of business ethics. For business people, halal certification provides benefits to increase consumer confidence and reach the global halal food market.